MODIFIKASI KARET ALAM SIKLIS DAN MALEAT ANHIDRAT DENGAN ADANYA PENAMBAHAN BENTONIT - CETIL TRIMETIL AMONIUM BROMIDA (CTAB) MENGGUNAKAN INISIATOR BENZOIL PEROKSIDA - Ahmad Hafizullah Ritonga; Barita Aritonang; Hendri Faisal (PROSIDING SEMINAR KIMIA, 2018)
Research on the modification of Cyclic Natural Rubber (CNR) and Maleat Anhydrate (MA) with addition of Bentonite - Cetyl Trimethyl Ammonium Bromide (CTAB) using Initiator of Benzoyl Peroxide (BPO) has been done, which aims to find out the appropriate method of modifying CNR and MA using BPO initiators to form CNR-g-MA, and mixed together with Bentonite-CTAB produces a CNR-g-MA/Bentonite-CTAB composite, which results are reviewed by FTIR spectroscopy and SEM analysis. This modification was carried out by dissolving 7 g of CNR with 20 mL of xylene at 45-55 ° C, then mixing the CNR solution with 3 g MA, followed by the addition of 5 phr BPO initiator and addition of 3 phr Bentonite-CTAB while stirring for + 1 hour at the same temperature. The results obtained were analyzed by FTIR spectroscopy showing sharp and strong absorption peaks at wave numbers 1437.80 cm-1, 1311.24 cm-1 and 849.73 cm-1 and the absence of the -OH group on the wavelength number 3598.51 cm-1 and 3411.92 cm-1 indicating Bentonite-CTAB has been mixed in CNR-g-MA. The morphological results with SEM show that Bentonite-CTAB is mixed in CNR-g-MA homogeneously. Keywords: Cyclic Natural Rubber, Maleat Anhydrates, Benzoyl Peroxide, Bentonite, Cetyl TrimethylAmmonium Bromide.